دور جودة التحاسب الضريبي في اكتشاف التطويع المصطنع للأرباح: (دراسة ميدانية من وجهة نظر إدارة التفتيش والمراجعة بديوان الضرائب بالسودان) - د. صالح حامد محمد علي; د. مزمل عوض طه أحمد (White Nile Journal for Studies and Research, 2026)
The study targeted mainly examine the role of the quality of tax settling accounts in the discovery of earning management in the financial reports submitted of settling accounts tax in Sudanese taxation chamber, to achieve this objective the researchers test a set of hypotheses that are related to the requirements and the quality of tax settling accounts and discovering the practice of earning management. The study found a number of results the most Important there were significant correlation between the quality of tax settling accounts in the discovery of earning management practices. the study recommended the need to the attention of the taxation chamber continuous professional development for employees running the inspection and review and the provision of appropriate screening process work environment. Key words:quality of tax settling accounts, earning management